Promoting Problem-Based Learning (PBL) in Engineering Courses at the Universiti Teknologi Malaysia - Mohd Yusof, Khairiyah (UNESCO International Centre for Engineering Education (UICEE), 2005)
In this paper, the authors describe the efforts in promoting the implementation of Problem-Based Learning (PBL) at the Universiti Teknologi Malaysia (UTM), Johor Bahru, Malaysia, which is essentially the groundwork phase of the University-wide PBL project. The move to train a core group of lecturers to implement PBL was initiated in 2002. The litmus test on the effectiveness and the possible applicability of PBL in engineering courses at the UTM was conducted in the first semester of the 2003/04 academic year in Process Control and Dynamics , a required subject for fourth year students in the Department of Chemical Engineering in the Faculty of Chemical and Natural Resources Engineering. The outcome of the pilot implementation was highly successful in that the Department allowed PBL to be implemented in other classes. This also encouraged other faculties to promote the implementation of PBL. Since then, there have been several implementations in the Faculty of Chemical and Natural Resources Engineering, the Faculty of Mechanical Engineering, the Faculty of Electrical Engineering, and the Faculty of Civil Engineering.